Preoperative Total Leukocyte Count: A Key Predictor for Better Optimization and Conversion Risk in Laparoscopic Cholecystectomy for Cholelithiasis: Preoperative Total Leukocyte Count: Laparoscopic Cholecystectomy for Cholelithiasis - Ahmed, Hafiz Waqas; Khanum, Rabia; Gauhar, Tooba Mahmud; Khan, Safiullah; Nafees, Rubab; Babar, Jahanzaib (Pakistan Journal of Health Sciences, 2025)
Gallstone disease requires laparoscopic cholecystectomy (LC) as the standard of care. Sometimes, the surgeon decides to convert LC to open cholecystectomy (OC) for patient safety. Several factors help us predict preoperatively whether there is any chance of conversion of LC to OC. The role of elevated total leucocyte count (TLC) as a predictor for conversion is being proposed. This study investigates the association between pre-operative TLC levels and conversion rates from LC to OC. Objective: To determine the association between increased TLC and conversion from LC to OC. Methods: This study was conducted at Al-Tibri Medical College Hospital, Karachi, over eighteen months from 1st July 2023 to 31st December 2024. A total of 230 patients were included. We selected 115 patients with TLC above 11.0x10^9/L and 115 patients with non-elevated TLC. All patients underwent LC, and conversions to OC were recorded. Data were analyzed using SPSS version 23.0. Mean and standard deviation were computed for numerical variables, and percentages for categorical variables. The chi-square test was applied to find the association between categorical variables. The relative risk (RR) was calculated to compare the risk of conversion of LC to OC among Elevated and Non-elevated TLC Groups. Results: The average age of patients was 31.82±10.06 years. The conversion risk was 117% higher in the elevated TLC group compared to the non-elevated TLC group (RR=2.17, 95%CI: 1.32-3.56). Conclusions: It was concluded that elevated pre-operative TLC is significantly associated with a higher risk of conversion from LC to OC, indicating its potential as a predictive factor for surgical planning.